Reflecting the audience : London theatregoing, 1840-1880 - Davis, Jim, 1949- (Studies in theatre history and culture., 2001)
This innovative work begins to fill a large gap in theatre studies: the lack of any comprehensive study of nineteenth-century British theatre audiences. In an attempt to bring some order to the enormous amount of available primary material, Jim Davis and Victor Emeljanow focus on London from 1840, immediately prior to the deregulation of that city's theatres, to 1880, when the Metropolitan Board of Works assumed responsibility for their licensing. In a further attempt to manage their material, they concentrate chapter by chapter on seven representative theatres from four areas: the Sur.